Nurses' Perceptions of Patient Safety Culture During the Pandemic in Covid-19 Referral Hospitals - Annisa Rahmi Galleryzki; RR Tutik Sri Hariyati; Kuntarti; Janes Jainurakhma (Jurnal Ilmiah Kesehatan, 2022)
Patient safety culture is essential in creating a safe and healthy hospital environment. This study aims to portray nurses' perceptions of patient safety culture during the Pandemic in COVID-19 Referral Hospitals. This paper was a descriptive study. The population was nurses working in inpatient, Covid-19 isolation, intensive, and emergency rooms. In addition, the sample was 268 nurses with a stratified random sampling. Data collection used a questionnaire using Google Forms. It consisted of the demographic characteristics of respondents (name, gender, age, marital status, working time, education, nurse position, levels of nursing, and patient safety training) also nurses' perception of patient safety culture. The Hospital Survey on Patient Safety Culture (HSOPC) was an instrument to assess patient safety culture. Data analysis used IBM SPSS Statistics version 22.0 to describe the mean, median, minimum, and maximum values and presentation. Results showed that the mean patient safety culture among nurses in COVID-19 referral hospitals was 147.09 (62.55%). In addition, the lowest dimension of patient safety culture was feedback and communication (31.75%), while the highest was an organizational improvement (73.16%). Thus, the patient safety culture in the COVID-19 referral hospital still needed improvement. A good patient safety culture can increase patient safety and the quality of health services. Therefore, hospital management should optimize all dimensions of patient safety culture to ensure patient safety. Future research could explore predisposing factors of patient safety culture